Caribbean Report 30-06-1995 - Richards, Ken (anchor); Crosskill, Hugh (correspondent); Camacho, Steven (interviewee); Benjamin, Winston (interviewee); Gower, David (correspondent); Sobers, Garfield (interviewee); Hughes, Hubert (interviewee); McIntyre, Allister (interviewee); Hutchinson, Peter (interviewee) (The British Broadcasting Corporation, 1995)
In this report: West Indies fastbowler Winston Benjamin has been axed from the squad currently touring England due to a lack of fitness and discipline. Steven Camacho, Chief Executive of the West Indies Cricket Board comments on the predominant reasons for the termination but Winston Benjamin contests the disciplinary side of it. Former West Indies captain Sir Gary Sobers talks about the state of West Indies cricket. Anguilla's Chief Minister Hubert Hughes wants Britain to fund an economic development programme for his island. Montserrat's Chief Minister Reuben Meade confirms the construction of a major private sector investment project with Britain and Brussels. The University of the West Indies (UWI) is moving to make its mark on the corridors of international academia. Death Watch, the UK-based organization, opposes the death penalty in the Caribbean region. Its Chairman Peter Hutchinson comments on its aim to nurture informed public opinion on the subject in the region.
1. Headlines with Ken Richards (00:00-00:45)
2. West Indies fastbowler Winston Benjamin axed from the West Indies squad due to lack of fitness and discipline (00:46-08:21)
3. Anguilla's Chief Minister wants the British government to fund an economic development programme for Anguilla (08:22-11:05)
4. Montserrat's Chief Minister holds talks for the construction of a major private sector investment project (11:06-11:40)
Keywords: Cricket -- West Indies; Cricket -- Tournaments -- England; Cricket players -- West Indies; Economic development -- Anguilla; Economic assistance, British -- Anguilla; Anguilla -- Politics and government; Investments, Foreign -- Montserrat; Economic development -- Government policy -- Montserrat; University and colleges -- Planning; Education, Higher -- Caribbean Area; Academic achievement -- Caribbean Area; Death row inmates -- Caribbean Area; Capital punishment -- Caribbean Area; Prison administration -- Caribbean Area